Typification and checklist of Colona names (Malvaceae: Grewioideae) - Gerace, Samuele (Phytotaxa, 2025)
An alphabetical list of all the correct names of the genus Colona, including those first validly published in Columbia, Diplophractum, and Microcos, is presented. Are provides details of all nomenclatural types, including thirty-one new typifications (twenty-five lectotypifications, and seven neotypifications), as well as one new synonymy and one new name.